Perlindungan konsumen dalam perbankan Syariah - anggraeni, Roro ajeng Dewi (Maliki Interdisciplinary Journal, 2025)
The purpose of this study is consumer protection in Islamic banking is a crucial component that helps to build trust and confidence among nasabah. In this regard,consumer protection is not limited to adhering to syariah principles; it also includes considerations of transparency, security,and safety in every transaction that is carried out.this study examines many strategies used by Islamic banks to protect consumers, including through sengketa mechanism,clear and accurat information about products and services,and protection from practical penipuan. It is believed that by integrating Islamic law and banking regulations, syariah banks will be able to create a safe and secure environment for their customers.the study’s findings indicate that, in addition to strengthening the foundation of the Islamic banking system, implementing sound consumer protection principles can increase nasabah’s market share.